Nucleosomes at the Dawn of Eukaryotes - Hocher, A; Warnecke, T (Oxford University Press, 2024)
Genome regulation in eukaryotes revolves around the nucleosome, the fundamental building block of eukaryotic chromatin. Its constituent parts, the four core histones (H3, H4, H2A, H2B), are universal to eukaryotes. Yet despite its exceptional conservation and central role in orchestrating transcription, repair, and other DNA-templated processes, the origins and early evolution of the nucleosome remain opaque. Histone-fold proteins are also found in archaea, but the nucleosome we know—a hetero-octameric complex composed of histones with long, disordered tails—is a hallmark of eukaryotes. What were the properties of the earliest nucleosomes? Did ancestral histones inevitably assemble into nucleosomes? When and why did the four core histones evolve? This review will look at the evolution of the eukaryotic nucleosome from the vantage point of archaea, focusing on the key evolutionary transitions required to build a modern nucleosome. We will highlight recent work on the closest archaeal relatives of eukaryotes, the Asgardarchaea, and discuss what their histones can and cannot tell us about the early evolution of eukaryotic chromatin. We will also discuss how viruses have become an unexpected source of information about the evolutionary path toward the nucleosome. Finally, we highlight the properties of early nucleosomes as an area where new tools and data promise tangible progress in the not-too-distant future.